Patient and Clinician Perspectives on Adolescent Opioid Use Disorder Treatment During a Pandemic: One Step Back, but Two Forward? - Stull, Samuel W; McKnight, Erin R; Bonny, Andrea E (JMIR Publications, 2020)
Opioid use disorder (OUD) is one of the most pressing public health problems in the United States and is highly prevalent among adolescents and young adults (AYAs). However, only a small percentage of AYAs with OUD ever receive treatment. Further, among those that do receive treatment, a substantial proportion of patients continue to struggle with OUD, and many prematurely drop out of treatment. These challenges have only been heightened in the face of the COVID-19 pandemic, but greater utilization of telehealth and mobile technologies by OUD patients may help counter these barriers, which ultimately may improve AYA OUD treatment in the postpandemic period. This viewpoint presents the perspective of a person in OUD recovery using online and mobile technology to support his own OUD recovery combined with thoughts from two clinicians supporting AYAs with OUD. Their perspectives may provide insights to help counter COVID-19-related consequences and offer clues to improving AYA OUD treatment in the long term.